Investigation of the Odours Emitted from Chemical Plants by Gas Chromatography-Mass Spectrometry† - Arjunan, V.; Subramanian, S.; Mohan (Asian Journal of Chemistry, 2010)
Odour escaping from the chemical, dye manufacturing and steel industries are a continual source of complaints by locals of nearly a decade. Although several precautions such as filtering system have been introduced by these industries, noxious smells still escape frequently whenever the filter system is saturated: Since the removal and regeneration of these filter systems is an expensive task, very little is done in this regard. Hence an attempt has been made in the present work to examine the compounds adsorbed on the filters using gas-chromatography with a mass-spectrometer detector. The components identified in the process are hydrocarbons, sulphur containing species, various arnines and arnides, aldehydes and ketones, aliphatic acids and esters, aliphatic alcohols, aromatic alcohols and phenol.